Evaluation of the Success of the Watershed Rehabilitation Project in Bombana Regency Based on Cook Method’s Runoff Coefficient - Ery Nuralamsyah; Mariana Marselina (Universitas Diponegoro, 2023)
Watersheds have an important role in managing rainwater. A good watershed can provide sufficient water for the community in the dry season and does not cause flooding in the rainy season. Therefore, watershed preservation is necessary as an effort to maintain or improve its function. Rehabilitation is an effort to restore, maintain, and improve the watershed function. In this study, rehabilitation was carried out in an area of 285 ha which cuts two watersheds, Langkapa and Poleang watershed. The success of this rehabilitation can be reviewed through the runoff coefficient before and after rehabilitation. The runoff coefficient is a value that expresses the percentage of rainwater that turns into surface runoff water. That value can be an indicator of the watershed quality. The determination of the runoff coefficient in this study used the Cook Method which considers four physical parameters, land cover, slope, soil infiltration, and surface deposit/flow density. The results showed the runoff coefficient decreased after the rehabilitation from 68.54% to 65.85% which means the rehabilitation has improved the watershed quality. But those change is not significant because the rehabilitation location actually is not the priority land (critical land) that needs rehabilitation.